2014
DOI: 10.1536/ihj.14-107
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Pioglitazone on Retardation of Persistent Atrial Fibrillation Progression in Diabetes Mellitus Patients

Abstract: SummaryThis study aimed to explore the effects of pioglitazone treatment on progression from persistent atrial fibrillation (AF) to permanent atrial fibrillation in diabetes mellitus (DM) patients and to investigate the possible mechanisms involved in those effects.A total of 146 diabetes mellitus (DM) patients with firstly identified persistent AF were selected. Seventy patients were randomized into the pioglitazone (30 mg/day) group and 76 into the placebo group. Pro-collagen type I carboxyterminal peptide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…CAV1 is upregulated by the transcription factor, PPARγ and activation of PPARγ by drugs such as pioglitazone also upregulates CAV1 expression [21]. Small studies have suggested that pioglitazone may prevent recurrence of AF following catheter ablation and prevent progression of AF in diabetic patients [22,23]. Our results suggest further clinical evaluation of pioglitazone and other PPARγ agonists in prevention of AF is warranted.…”
Section: Discussionmentioning
confidence: 76%
“…CAV1 is upregulated by the transcription factor, PPARγ and activation of PPARγ by drugs such as pioglitazone also upregulates CAV1 expression [21]. Small studies have suggested that pioglitazone may prevent recurrence of AF following catheter ablation and prevent progression of AF in diabetic patients [22,23]. Our results suggest further clinical evaluation of pioglitazone and other PPARγ agonists in prevention of AF is warranted.…”
Section: Discussionmentioning
confidence: 76%
“…After careful assessment, seven studies (three RCTs [12, 14, 17] and four observational studies [13, 15, 16, 18]) comprising 130,854 diabetic patients (11,781 in the treatment and 119,073 in the control group) were included in the final meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [12, 15, 17] examined the relationship between pioglitazone use and AF, while two other [14, 16] studied rosiglitazone use. The remaining two studies [13, 18] reported data regarding the use of pioglitazone, rosiglitazone and troglitazone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations